Teenage Pregnancy and the Quest for a Place for Pregnant Girls: A Study on the Rule of Pregnant Student Expulsion in Yogyakarta, Indonesia - Desintha Dwi Asriani (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This study attempts to reveal the problem that lies behind the discourse of teenage pregnancy in relation to the politics of place. It primarily derives from the tendency of a number of schools in Indonesia to expel pregnant students. The quest of a “place” simply refers to public spaces that are more contested for pregnant girls. However, the term place is not limited to its literal definition of physical location. Rather, it involves more complex dimensions such as gender dichotomy, body politics, and the politics of modernity. By examining interview data acquired from several school teachers and girls, this research will contextualize such case within the paradoxical relation between the conception of modernity in delivering the idea of progress and participation, and the extent to which the maternal body is mobilized within the discourse of gender dichotomy in public.